An Expanded Perspective on Agenda-Setting Effects. Exploring the third level of agenda setting - Guo, Lei (2022)
Agenda-setting has evolved from a focus on media effects on the public's perception of the most important issues of the day to a theory elaborating a hierarchy of communication effects. Its core is three levels of agenda-setting. The initial two levels were introduced during the first decade of research. Level three is recent. Evidence from the initial studies on this expanded view of agenda setting supports the Network Agenda Setting Model. This theoretical model asserts that the news media can bundle sets of objects or attributes and make these bundles of elements salient in the public's mind simultaneously.